Pengaruh Motivasi, Budaya Organisasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Vendor Cartertag.Id - Annisa Novitalia Ismail; Harries Madiistriyatno; Eddy Hermawan Hasudungan (Journal of Innovative and Creativity, 2025)
The objectives of this study: 1) To find out the influence of motivation on vendor employees Cartertag.Id 2) to find out the organizational culture on vendor employees Cartertag.Id 3) to find out the influence of work discipline on vendor employees Cartertag.Id 4) This research is a quantitative research, descriptive and associative type. The population in this study is Cartertag.Id Vendor Employees. The sampling technique used was a sample using Random Sampling, a sample of 30 Employees at the Vendor Cartertag.Id as respondents in this study. Results in this study: 1) There is an effect of Motivation on Employee Performance, it is proven that the tcal value for the Motivation variable (X1) is 3.382 while the ttable value for N = 30 is 2.042. So 3.382 > 2.042, then H0 is rejected and Ha is accepted, it can be stated that Motivation (X1) has a significant effect on Employee Performance (Y) 2) There is an influence of Organizational Culture on Employee Performance, it is proven that the tcal value for the Organizational Culture variable (X2) is 2,877 while the ttable value for N = 30 is 2,042. So 2,877 > 2,042, then H0 is rejected and Ha is accepted, it can be stated that Organizational Culture (X2) 3)There is an influence of Work Discipline on Employee Performance, it is proven that the tcal value for the Work Discipline variable (X3) is 2,563 while the ttable value for N = 30 is 2,042. So 2,563 > 2,042, then H0 is rejected and Ha is accepted, it can be stated that Work Discipline (X3) has a significant effect on Employee Performance (Y) 4) There is an influence of Communication, Organizational Culture and Work Discipline together on Employee Performance, as evidenced by the ANOVA test obtained a Fcal value of 21,631, while Ftabel (α 0.05) for N = 30 is 2.97. So the Fcal > of Ftabel (α 0.05) or 12,580 > 2.97 with a significant level of 0.000 because 0.000 < 0.05, then it can be said that Motivation (X1), Organizational Culture (X2) and Kejra Discipline together or simultaneously have a positive effect on Employee Performance (Y)